Revenge of the aesthetic : the place of literature in theory today - Clark, Michael, 1950- (University of California Press, 2000)
This collection of essays showcases the work of some of the most influential theorists of the last 30 years of the 20th century as they grapple with the question of how literature should be treated in contemporary theory. The contributors challenge trends that have recently dominated the field - especially those that emphasize social and political issues ofver close reading and other analytic methods traditionally associated with literary criticism.